Trends in the transformation of plant ontogenesis under global climate warming - Ihor Kovalenko; Sergey Butenko; Anatoly Zhezhkun; Ihor Porokhniach; Ozodbek Abduraimov; Hanna Klymenko (Agraarteadus, 2022)

(untitled)
Observations of the process of ontogenesis in a group of woody plants and forest grass in the phytocenoses of the Ukrainian Polesie of Sumy region with their division into boreal and nemoral species were done. Found that in the last two decades, nemoral plant species begin vegetation earlier and pass the first phases of the ontogenetic cycle faster than boreal species. Changes in plant ontogenesis, in turn, lead to changes in the population characteristics of plant species: the number of individuals in the population, the size and configuration of the population field and the ontogenetic and vital spectra of populations changed. There has been a tendency to regular changes in the ontogenetic spectra of both nemoral and boreal plant species, but their nature was different. In nemoral plant species, the proportion of juvenile and immature individuals in the ontogenetic spectra increased and populations acquired the character of invasive, reflecting the process of progressive strengthening of their position in phytocenoses. In populations of boreal species, on the contrary, the ageing process accelerated – the proportion of old generative, senile and subsenile individuals increased.